The synthesis, structure, and magnetic properties of nickel (II) 6-coordinate species with several substituted aniline ligands. (15th May 2021) - Meehan, Katherine L.; Fontaine, Devon FA; Richardson, Alistair D.; Fowles, Samantha M.; Mukda, Benjamin; Monroe, Jeffrey C.; Landee, Christopher P.; Dickie, Diane A.; Turnbull, Mark M.; Jiang, Shu; Xiao, Fan
Graphical abstract: Reaction of Ni(II) bromide and chloride with a series of substituted aniline ligands produced a family of 6-coordinate complexes. Magnetic susceptibility measurements show both single-ion anisotropy and mean-field magnetic interactions. Abstract: A family of Ni(II) halide complexes of substituted aniline derivatives were prepared and studied via single-crystal X-ray diffraction and variable temperature magnetic measurements: [Ni(4-Mean)4 Cl2 ] 1, [Ni(4-Clan)2 Cl2 (MeOH)2 ] 2, [Ni(4-Clan)2 Br2 (EtOH)2 ] 3, [Ni(4-Clan)4 Br2 ] (4-Clan) 4, [Ni(4-Clan)2 Br2 (H2 O)2 ] 5, [Ni(4-MeOan)2 Br2 (H2 O)2 ] 6, [Ni(3-MeOan)4 Cl2 ] 7, [Ni(3-MeOan)4 Br2 ] 8, [Ni(4-MeOan)4 Cl2 ] 9, [Ni(4-MeOan)4 (H2 O)2 ](Br)2 10, and [(4-MeOan)2 (DMSO)4 Ni](Br)2 11 (4-Mean = 4-methylaniline, 4-Clan = 4-chloroaniline, 3-MeOan = 3-methoxyaniline, 4-MeOan = 4-methoxyaniline). All complexes are six-coordinate, filling the coordination sphere with a combination of halide ions, aniline-based ligands and/or solvent molecules. The complexes demonstrate variable stability once removed from the mother liquor with loss of coordinated solvent molecules being common. Analysis of the magnetic properties of the compounds shows the presence of single-ion anisotropy, weak interactions, or a combination thereof.